Gunfight at the O.K. Corral [videorecording (DVD)] - Douglas, Kirk, 1916-2020-; Lancaster, Burt, 1913-1994; Fleming, Rhonda, 1923-2020-; Ireland, John, 1914-1992; Van Fleet, Jo, 1914-1996 (Paramount Home Entertainment, 2017)
Frontier lawman Wyatt Earp joins his three brothers in their feud against the villainous Clanton gang, a local clan of cattle thieves in Tombstone, Arizona. When Earp defends the sickly gambler John 'Doc' Holliday and puts a stop to the Clanton's lawlessness, the ruthless outlaws seek revenge and murder one of Earp's brothers. This leads the men into the most devastating showdown in wild West history.